Positive Influence of Entrepreneurship Mobile Media Implementation on Entrepreneurial Interest & Learning Outcomes - Yunus, Yuliawati; Ganefri; Yulastri, Asmar (The Indonesian Journal of Computer Science, 2023)
Blended learning is very important today, and various platforms are used to achieve reasonable learning goals in education, ranging from low to high levels. Different learning platforms are implemented in e-learning systems, mobile applications, and other interactive media. The venue is only sometimes able to help students in learning thoroughly. So that there is a need for learning style adjustments to the learning process. This study uses an Android-based entrepreneurship learning media application to determine the results of entrepreneurial education and students' entrepreneurial interests. The type of research used was a quasi-experiment with a population of 406 students. Samples were taken using purposive sampling techniques. The instruments used in this study are objective tests and questionnaires of entrepreneurial interest. The analysis technique used was Anova with test F. The results revealed a positive influence between implementing entrepreneurial mobile media on increasing entrepreneurial interest and student learning outcomes